Performance analysis of digital watermarking on medical images / Syaza ‘Aqilah Zul Wizaratain - Zul Wizaratain, Syaza ‘Aqilah (2020)
Digital watermarking technique is a method used to embed messages into digital multimedia contents with the purpose of concealing the presence messages from naked eyes. This research project implements digital watermarking technique on grey scale medical images using Least Significant Bit (LSB) algorithm. The patient information such as patient personal data and diagnostic result are embedded into the medical images before transmitting to receivers as part of telemedicine process. The purposed project is tested in term of image quality using PSNR and MSE for watermarked medical images after the transmission. The transmission consists of three different mediums- WhatsApp, Gmail and Dropbox, all watermarked medical images are sent and evaluated. The entire processes are run in MATLAB R2019b. The results analysis obtained shows that medical images sent thru Dropbox is better compared to the other two mediums because it has the highest PSNR and lowest MSE values that indicated the medical images are in a good condition.